Behavioral Outcomes Following Brain–Computer Interface Intervention for Upper Extremity Rehabilitation in Stroke: A Randomized Controlled Trial - Remsik, Alexander B.; Dodd, Keith; Williams, Leroy; Thoma, Jaclyn; Jacobson, Tyler; Allen, Janerra D.; Advani, Hemali; Mohanty, Rosaleena; McMillan, Matt; Rajan, Shruti; Walczak, Matt; Young, Brittany M.; et al. (Frontiers in Neuroscience, 2018)
Stroke is a leading cause of persistent upper extremity (UE) motor disability in adults. Brain-computer interface (BCI) intervention has demonstrated potential as a motor rehabilitation strategy for stroke survivors. This sub-analysis of ongoing clinical trial (NCT02098265) examines rehabilitative efficacy of this BCI design and seeks to identify stroke participant characteristics associated with behavioral improvement. Stroke participants (n = 21) with UE impairment were assessed using Action Research Arm Test (ARAT) and measures of function. Nine participants completed three assessments during the experimental BCI intervention period and at one-month follow-up. Twelve other participants first completed three assessments over a parallel time-matched control period and then crossed over into the BCI intervention condition one-month later. Participants who realized positive change (≥1 point) in total ARAT performance of the stroke affected UE between the first and third assessments of the intervention period were dichotomized as ‘Responders’ (<1 = ‘Non-Responders’) and similarly analyzed. Of the 14 participants with room for ARAT improvement, 64% (9/14) showed some positive change at completion and approximately 43% (6/14) of the participants had changes of Minimal Detectable Change (MDC = 3pts) or Minimally Clinical Important Difference (MCID = 5.7 points). Participants with room for improvement in the primary outcome measure made significant gains in ARATtotal score at completion (ΔARATtotal = 2, p = 0.028) and one-month follow-up (ΔARATtotal = 3.4, p=0.0010), controlling for severity, gender, chronicity, and concordance. Secondary outcome measures, SISmobility, SISadl, SISstrength and 9HPTaffected also showed significant improvement over time during intervention. Participants in intervention through follow-up showed a significantly increased improvement rate in SISstrength compared to controls, (p=0.0117) controlling for severity, chronicity, gender, as well as the individual effects of time and intervention type. Participants who best responded to BCI intervention, as evaluated by ARAT score improvement, showed significantly increased outcome values through completion and follow-up for SISmobility (p=0.0002, p=0.002) and SISstrength (p=0.04995, p=0.0483). These findings may suggest possible secondary outcome measure patterns indicative of increased improvement resulting from this BCI intervention regimen as well as demonstrating primary efficacy of this BCI design for treatment of UE impairment in stroke survivors.